As estratégias de credibilidade das organizações de fact-cheking brasileiras em reação às fake news no contexto de crise do jornalismo profissional - Müller, Kauane Andressa (2020)
This dissertation analyses the credibility strategies of the Brazilian factchecking organizations Aos Fatos, Lupa, and Estadão Verifica. Interviews with reporters and editors from each factchecking platform were conducted, in addition to an in loco observation in Estadão Verifica newsroom and analysis of documents published by the organizations on their own websites. The corpus analysis was based on the manifested discursive strategies, according to Charaudeau (2006). The analysis also allowed the collected data to indicate new categories of strategies, elaborated throughout the work. Authenticity, explanation, and performance in partnerships were present in all checking platforms; verisimilitude, use of tags, and getting closer to readers were found in two organizations; and the demonstration of impartiality and the automation of the process appeared in just one. The reflection developed was based on the comprehension of journalism as a social form of knowledge crystallized in the singular (GENRO FILHO, 1987). From the discussion of the crisis of the professional journalism model, we present the centrality of the discussions on fake news and factchecking as an initiative to verify speeches and information from social networks (PALÁCIOS, 2019). These discussions are put into dialogue with the perspective of Communication and Work (FIGARO, 2018), seeking to understand the changes that the hegemonic model of journalism suffers in this context of crisis. It was possible to identify some characteristics of precarious work relationships in factchecking organizations. We were also able to indicate in the speeches of the interviewed professionals an attempt to distance and differentiate from the traditional press, in which factchecking organizations seem to be in search of credibility, built on the value of transparency and based on correspondence with reality.